Resilience? Insights into the role of Critical Infrastructures Disaster Mitigation Strategies - Bouchon, Sara; Di Mauro, Carmelo (TeMA - Journal of Land Use, Mobility and Environment, 2012)
Critical infrastructures (CI) systems provide essential services “for the maintenance of critical societal functions, including the supply chain, health, safety, security and economic or social well-being of the people” (European Commission, 2008). These systems are exposed to a great number of hazards and threats, which may result in severe consequences for the population, the socio-economic system, and the environment. The issue is particularly relevant at urban level, where the disruption of one CI system can propagate to the other systems and paralyze the entire area. It is therefore necessary, not only to protect CIs through Critical Infrastructure Protection (CIP) strategies, but also to enhance the resilience of these areas. This article aims thus at providing some insights related to the evolution of the critical infrastructures disaster mitigation strategies from the sole protection towards resilience: what kind of strategies based on resilience can be developed to address CIs disruption at local or regional level? To what extent do these strategies contribute to increase the resilience level of the entire urban or metropolitan area? The first section focuses on the urban critical infrastructures systems as well as on the way their disruption can impact urban areas. The second section provides with some examples of key measures to operationalize resilience in the field of critical infrastructure disaster mitigation strategies. The last section highlights how the key measures developed to enhance the resilience against CI disruptions can benefit also to broader urban resilience.